Cooperative/Collaborative Learning - Gillies, Robyn M. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book brings together a diverse range of international scholars to highlight recent developments in research on collaborative learning. The emphasis is on research that has a strong evidence base for the work that is presented and includes empirical studies, best evidence synthesis of the relevant research, case studies, and theoretical reports. It also highlights how different technologies have been used to facilitate group interaction, dialogue, and learning. There is much to be gained by sharing and learning about what happens in different disciplines and contexts and how different collaborative pedagogies can be implemented when needed to promote understanding and learning. This book will have strong appeal to pre-service and experienced teachers and researchers who are interested in how different collaborative pedagogies can be embedded in course curricula to promote student engagement and learning.